Leclercia adecarboxylata C12, The Newly Isolated Cellulose-degrading Bacteria from Indonesian Coffee Pulp - Agustin Krisna Wardani; Ajeng Astrini Brahmanti; Erryana Martati (Bogor Agricultural University, Indonesia, 2023)
Culturable cellulose-degrading microorganisms were collected from Arabica coffee pulp in East Java, Indonesia. Fifty isolates were obtained, and thirty-three isolates showed hydrolyzing zone on Carboxy Methyl Cellulose agar plates after Congo-Red staining. The highest specific CMCase activity was observed by isolates C12, identified as Leclercia adecarboxylata based on 16S-rRNA gene sequence analysis. SDS-PAGE of Leclercia adecarboxylata C12 cellulase revealed two bands with a molecular mass of 95.49 and 81.28 kDa, respectively. Activity gel analysis showed the cellulolytic ability of Leclercia adecarboxylata C12 cellulase by clear zone formation. The optimal CMCase activity was achieved at 50°C and pH 9, and the activity retained 47% of its initial activity after incubation at 50°C for 90 minutes. The purified enzyme remains stable from pH 5 to 10, with 77% of its maximum activity. The activity of CMCase was stimulated by the presence of K+, Ca2+, Mg2+, and Fe3+, while SDS and EDTA reduced its activity. The current study shows that the thermostable-alkalophilic cellulase produced by Leclercia adecarboxylata C12 is very promising for industrial applications.